2018
DOI: 10.3389/fmicb.2018.01969
|View full text |Cite
|
Sign up to set email alerts
|

Blood or Serum Exposure Induce Global Transcriptional Changes, Altered Antigenic Profile, and Increased Cytotoxicity by Classical Bordetellae

Abstract: The classical bordetellae sense and respond to a variety of environments outside and within their mammalian hosts. By causing inflammation and tissue damage, we reasoned that bordetellae are likely to encounter components of blood and/or serum during the course of a respiratory infection, and that detecting and responding to these would be advantageous. Therefore, we hypothesized that classical bordetellae have the ability to sense and respond to blood or serum. Blood or serum exposure resulted in substantial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(54 citation statements)
references
References 60 publications
(69 reference statements)
3
49
2
Order By: Relevance
“…Previous studies described the influence of whole blood on gene expression in different pathogenic bacteria [111][112][113][114][115][116], who examined Bacillus anthracis, Bordetella pertussis, Streptococcus pyogenes, Staphylococcus aureus, Streptococcus agalactiae, and Enterococcus faecalis, respectively. The type of blood used ranged from bovine [111] to horse [112] to sheep [116] to human [113][114][115].…”
Section: Wb Influenced Gene Expression In P Aeruginosa and Other Bacmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies described the influence of whole blood on gene expression in different pathogenic bacteria [111][112][113][114][115][116], who examined Bacillus anthracis, Bordetella pertussis, Streptococcus pyogenes, Staphylococcus aureus, Streptococcus agalactiae, and Enterococcus faecalis, respectively. The type of blood used ranged from bovine [111] to horse [112] to sheep [116] to human [113][114][115].…”
Section: Wb Influenced Gene Expression In P Aeruginosa and Other Bacmentioning
confidence: 99%
“…Previous studies described the influence of whole blood on gene expression in different pathogenic bacteria [111][112][113][114][115][116], who examined Bacillus anthracis, Bordetella pertussis, Streptococcus pyogenes, Staphylococcus aureus, Streptococcus agalactiae, and Enterococcus faecalis, respectively. The type of blood used ranged from bovine [111] to horse [112] to sheep [116] to human [113][114][115]. Additionally, the expression of the genes of the target organism were examined at radically different times, most ranging from time of inoculation (time 0) to 120 min [112][113][114][115][116] to as long as 4 h [111].…”
Section: Wb Influenced Gene Expression In P Aeruginosa and Other Bacmentioning
confidence: 99%
See 1 more Smart Citation
“…The classical Bordetella species, Bordetella bronchiseptica, B. pertussis, and B. parapertussis, can all sense blood and serum components and respond with altered expression of various antigens and increased expression of various known virulence factors and iron scavenging systems. They also change phenotypically, increasing their cytotoxicity likely due to the increased expression of virulence factors such as ACT and/or the type 3 secretion system (T3SS) [35]. Gonyar et al studied those host factors that increase the expression of a particular toxin and found that exposure of B. pertussis to Fetal Bovine Serum, albumin, and calcium increases ACT levels, suggesting that B. pertussis can sense the presence of those two specific serum components and respond by increasing production of ACT which not only works as a hemolysin but also plays a major role in the down-regulation of the host inflammatory response [16].…”
Section: Bordetella Respond To Host Environmentmentioning
confidence: 99%
“…The bsc -encoded genes of the Bordetella injectosome are induced during infection, and are responsive to blood or serum exposure, and increased CO 2 concentrations (Gaillard et al, 2011 ; Hester et al, 2012 ; Bibova et al, 2015 ; Gestal et al, 2018 ; Van Beek et al, 2018 ; Wong et al, 2019 ). Other stimuli that can activate T3SS expression and secretion in bordetellae are the stringent response induced by iron limitation and/or starvation for carbon source, as depicted in Figure 4 (Brickman et al, 2011 ; Kurushima et al, 2012b ; Hanawa et al, 2016 ).…”
Section: Type III Secretion Regulation In Bordetellamentioning
confidence: 99%